Feasibility of De-carbonization of Air-transportation to and from the Island of Crete, Greece - Vourdoubas , John (Current Advances in Geography, Environment and Earth Science Vol. 1, 2021)
The clean energy transition is an important and urgent issue in European islands contributing in the global effort for climate change mitigation. Island of Crete, Greece is a popular tourist destination while the most of visitors arrive and depart with aircrafts. Tourism industry dominates in Cretan economy contributing at around half of the regional income. Aim of the current study is to investigate the possibility of de-carbonizing the air-transportation to and from Crete. Air-transportation has a share at 10.62% in the total carbon emissions in the island while other studies have estimated higher values. This is higher than the estimated share of carbon emissions in aviation at 2-3% of the overall carbon emissions worldwide. Various technological and non-technological approaches for de-carbonizing aviation are examined including improvements in aircraft’s standards, use of sustainable aviation fuels, offsetting carbon emissions and developing new policies discouraging the frequent use of air travelling. The feasibility and the impacts of these methods are mentioned indicating that de-carbonization is difficult in the short and medium term. Production of sustainable aviation fuels including bio-fuels and electro-fuels in the required quantities and in competitive prices is not foreseen soon. Developing new policies that increase the cost of air travelling and promote alternative sustainable modes in transportation will have undesired impacts in the island’s tourism industry. On the contrary de-carbonization in other socio-economic sectors in Crete comprising electricity generation, production of heat and cooling and transportation inside the island is easier than in air-transportation.